Cross-national research in audiovisual translation: Some methodological considerations - Perego, Elisa (Journal of Audiovisual Translation, 2018)
Cross-national research is a research methodology that aims to make comparisons across countries. Nowadays, cross-national research is growing, especially in some social science disciplines such as sociology, political science, geography, and economics. However, it has not yet steadily entered the field of audiovisual translation (AVT). Despite its theoretical and methodological challenges (Hoffmeyer-Zlotnik & Harkness, 2005), cross-national research could be used successfully in AVT to investigate long-debated issues. These issues include, but are not restricted to, the reception of a given AVT method or strategy, and the different ways in which the translation process is accomplished in different countries. In this contribution, I will outline both theoretical and methodological debates in comparative cross-national research and apply them to AVT. After that, I will briefly present the results of a cross-national study (Perego et. al, 2016) designed to analyse the subtitle reception comparing the way the process takes place in different countries with different AVT traditions. The discussion of the study will contribute to assessing the potential strengths of cross-national research in AVT, thus offering indications on future methodological developments and enabling future and more rigorous international comparisons.